Preparation of non-noble metal based catalysts supported on carbon for PEMFC cathodes - Sarakonsri T. (2014)
Since non-noble metal-based catalysts have more activity and selectivity in four electron oxygen reduction than platinum-based catalysts for PEMFC cathodes, the development of non-noble metal-based catalysts has been of interest. Iron-based non-noble metal catalysts were prepared by supporting various oxides and tetraphenylporphyrin complexes of iron on carbon supports by a chemical process followed by heat treatment at various temperatures. Depending on these procedures, Fe3O4 and Fe-tetraphenylporphyrin catalysts supported on carbon were obtained. X-ray diffraction patterns of both Fe3O4 and Fe-tetraphenylporphyrin based catalysts indicated the crystallographic structure of Fe3O4; however, selected area diffraction patterns obtained from the TEM technique showed the Fe3N phase in Fe-tetraphenylporphyrin catalysts supported on carbon. Moreover, TEM images of Fe3O4 based catalysts showed a smaller particle size and more uniform distribution than Fe-tctraphenylporphj rin-based catalysts. Among the catalysts prepared, Fe-tetraphenylporphyrin catalyst supported on carbon with a heat treatment at 600 °C showed the highest electrochemical activity in an oxygen reduction reaction.